2003
DOI: 10.1287/mnsc.49.3.312.12739
|View full text |Cite
|
Sign up to set email alerts
|

Using Neural Network Rule Extraction and Decision Tables for Credit-Risk Evaluation

Abstract: C redit-risk evaluation is a very challenging and important management science problem in the domain of financial analysis. Many classification methods have been suggested in the literature to tackle this problem. Neural networks, especially, have received a lot of attention because of their universal approximation property. However, a major drawback associated with the use of neural networks for decision making is their lack of explanation capability. While they can achieve a high predictive accuracy rate, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
200
0
11

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 412 publications
(229 citation statements)
references
References 19 publications
0
200
0
11
Order By: Relevance
“…We use a decision tree for the following two reasons. First, the inherent transparency and interpretability of decision tree models help users follow the path of the tree and understand the classification rules step by step (e.g., Baesens et al 2003;Zhou and Jiang 2004). Second, studies such as Goto et al (2008), Long et al (1993), and Rudolfer et al (1999) have shown that decision tree models have a better accuracy rate for our sampling method than logistic models.…”
Section: Feldman and Sanger 2006) For Example Text Mining Techniquementioning
confidence: 99%
“…We use a decision tree for the following two reasons. First, the inherent transparency and interpretability of decision tree models help users follow the path of the tree and understand the classification rules step by step (e.g., Baesens et al 2003;Zhou and Jiang 2004). Second, studies such as Goto et al (2008), Long et al (1993), and Rudolfer et al (1999) have shown that decision tree models have a better accuracy rate for our sampling method than logistic models.…”
Section: Feldman and Sanger 2006) For Example Text Mining Techniquementioning
confidence: 99%
“…Data mining is a well-known and often suitable solution to big data problems involving risk such as credit risk modelling (Baesens et al, 2003), churn 5 A C C E P T E D M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 99%
“…The German credit data are obtainable from a website. The data consist of 1000 records of personal loans, and the input variables for one record include 7 numerical data and 13 categorical data [3,22].…”
Section: Applications To German Credit Datamentioning
confidence: 99%
“…Even though there are systems oriented to linguistic expressions, such as ID3, these systems usually need multiple clusters to distinguish between clusters (called pair-samples). For example, if we find a linguistic description for a cluster having "good" as a prescribed value, we also need a cluster having "bad" as a prescribed value [3][4][5][6]. Thus, these methods cannot be directly used to describe the features of a single isolated cluster.…”
Section: Introductionmentioning
confidence: 99%